Contradictions in mathematical modeling with digital technologies (2022)
RESUMEN: This article presents an analysis of contradictions expressed by pre-service mathematics teachers when performing two modeling tasks using their own technological devices. The study is based on theoretical aspects of contradictions in the fields of expansive learning and modeling with digital technologies. Technology and modeling tasks were designed and tested with 14 participants in a mathematical modeling course offered to pre-service teachers in a Colombian university. Linguistic cues were used to carry out a thematic analysis for identifying contradictions in discursive manifestations. The results show how specific contradictions in modeling processes with technology are manifested by students and the kind of transformations they promote, as well as the changes that occur in how tasks are performed, and how students develop an idea of technology that goes beyond its traditional conception as a tool. The findings show the influence of other activity systems on the development of these processes and the need for future studies in learning research.